Live streaming commerce as communication media at Social Bread - Dinansyah, Fakhriy; Susilo, Daniel; Berto, Agustinus Rusdianto (Universitas Bunda Mulia, 2024)
Live streaming commerce is the most up-to-date promotional tool connecting sellers and buyers. Social Bread utilizes this phenomenon as an institution that provides services for businesses to optimize product sales through the live-stream commerce method. Social Bread is a medium that bridges the buying and selling process. Much research on similar topics has been conducted, especially from China and the United States. However, little has been done in Indonesia, even though Indonesian businesses and society widely use this feature. This research aims to determine how live-streaming commerce is implemented and how the institution implementing live-streaming commerce becomes a communication medium for conveying messages to the audience. This research uses a qualitative case study methodology through interview techniques with the CEO, VP Operations, and Streamer from Social Bread. As a result, live streaming commerce embodies the Communicator – Medium – Communicator communication process, namely the business represented by the Streamer as the Communicator, an online shopping platform with live streaming features mediated by Social Bread as the medium, and the audience as the Communicant. The process of preparing live-stream commerce on Social Bread starts from implementing the client's brief by the Streamer to get the predicted results: increasing sales from live streaming. The consumers' cognitive responses previously in the audience are recorded, and a report is made to be presented to the client as evaluation material.